Minimum threshold for establishment and dispersal of Lilioceris cheni (Coleoptera: Chrysomelidae): a biological control agent of Dioscorea bulbifera. Issue 6 (3rd June 2018) - Lake, Ellen C.; Smith, Melissa C.; Rayamajhi, Min B.; Pratt, Paul D.; Dray, F. Allen
ABSTRACT: The successful establishment or failure of a new population is often attributed to propagule pressure, the combination of the number of independent introduction events, and the number of individuals released at each event. The design of optimal release strategies for biological control agents benefits from an understanding of the impact of propagule pressure on the species being released. The dispersal rate of individuals from nascent population foci can also affect establishment success. We assessed the minimum threshold for establishment and measured dispersal of Lilioceris cheni (Coleoptera: Chrysomelidae), a biological control agent for Dioscorea bulbifera (Dioscoreales), air potato. Replicated releases of 10, 50, and 100 adults of L. cheni were conducted on the east and west coasts of south Florida. Dispersal was measured from 19 of these sites plus 19 additional release locations in south and central Florida. Lilioceris cheni established populations from all three release sizes with no apparent influence of site location. Releases of 10, 50, and 100 adults resulted in 50%, 67%, and 85% establishment, respectively. Beetles dispersed an average of 1.41 ± 0.515 km/yr. Dispersal distance was significantly affected by the time since release but not the number of individuals released. Our results suggest that future releases of 100 individuals could be spaced several kilometres apart on the landscape to facilitate rapid colonisation of D. bulbifera infestations.